ESTIMATION OF VIBRIO SPECIES INCIDENCES AND ANTIBIOTIC RESISTANCE IN DIARRHEA PATIENTS. - Thakur, Nutan; Changotra, Harish; Shrivastava, Rahul; Grover, Neelam; Vashistt, Jitendraa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Diarrheal diseases are globally important public health concern due to high morbidity and mortality rates among all age groups. Incidences and antimicrobial resistance patterns of Vibrio species are either underreported or overlooked in low-to-middle income countries. The present study is a hospital surveillance conducted to estimate the incidences of Vibrio infections in diarrhea. Methods: A total of 572 diarrheal stool specimens were collected from two major hospitals and investigated using bacteriological tests coupled with molecular assays for characterization of Vibrio species. Kirby-Bauer's disk diffusion method was utilized to monitor antibiotic resistance against different antibiotic classes. Results: Biochemical and molecular analysis of isolates revealed that Vibrio species accounted for about 5% of diarrheal incidences. Higher rates of Vibrio spp. infections were observed among adolescent and adult age groups than children and elderly. Seasonal distribution analysis showed uniform Vibrio spp. infections throughout the year; however, frequency peaks were observed during rainy seasons. Vibrio spp. showed sensitivity for most antibiotics classes: Quinolones, aminoglycosides, and carbapenems; however, alarming resistance rates were observed against cephalosporins and nalidixic acid. Conclusion: The present study provides credible estimates of Vibrio incidences and resistance pattern in diarrheal patients. Our findings will help in establishing trends in diarrhea etiology and management of severe diarrhea cases.